Do minimum wages stimulate productivity and growth? - Joseph J. Sabia (IZA World of Labor, 2015)
Proponents of minimum wage increases have argued that such hikes can serve as an engine of economic growth and assist low-skilled individuals during downturns in the business cycle. However, a review of the literature provides little empirical support for these claims. Minimum wage increases redistribute gross domestic product away from lower-skilled industries and toward higher-skilled industries and are largely ineffective in assisting the poor during both peaks and troughs in the business cycle. Minimum wage-induced reductions in employment are found to be larger during economic recessions.
Keywords: J38; J31; 330; minimum wages; business cycle; productivity; poverty